Method for preparing weather-resistant polyimide insulation film for bus duct by blending modification

CN122685929BActive Publication Date: 2026-10-27SESRIC (CHENGDU) BUSWAY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611177037.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

然而,现有改性方案中,纳米粒子在聚酰亚胺基体中的团聚问题始终未能得到良好解决,简单机械搅拌难以实现纳米尺度的均匀分散,团聚体往往成为应力集中点和电场畸变区,反而削弱薄膜的绝缘性能与力学性能

Benefits of technology

本发明创造性地采用含氟烷基硅烷低聚物与纳米二氧化钛分散液作为共混改性组分,并将其引入聚酰胺酸溶液体系中进行高剪切机械共混。含氟烷基硅烷低聚物含有活性硅羟基或可水解烷氧基团,在共混及后续亚胺化高温处理过程中,能够与聚酰胺酸分子链上的羧基或羟基发生缩合反应,以化学键合方式接枝到聚酰亚胺分子骨架上,实现含氟组分的永久性固定,避免了物理共混带来的含氟助剂迁移析出问题。与此同时,纳米二氧化钛表面的活性羟基同样可与含氟烷基硅烷低聚物发生偶联反应,形成有机-无机交联网络结构,这种结构在薄膜内部构建起立体的化学交联体系,显著增强了改性组分与基体之间的界面结合强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685929B_ABST
    Figure CN122685929B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of insulating film material preparation, and discloses a preparation method of weather-resistant polyimide insulating film for bus ducts through blending modification. The method comprises the following steps: aromatic dianhydride monomers and aromatic diamine monomers are subjected to polycondensation reaction in an aprotic polar solvent to generate a polyamide acid solution; fluorine-containing alkyl silane oligomers and nano titanium dioxide dispersion liquid are added into the solution to be subjected to mechanical shearing blending, so that a modified polyamide acid blending solution is obtained; after the blending solution is cast into a film, the film is subjected to imidization treatment under the protection of an inert atmosphere through step-by-step temperature rising, so that a blending modified polyimide film is obtained. Through the coupling and modification of the fluorine-containing alkyl silane oligomers, the nano titanium dioxide is stably dispersed in the polyimide matrix, the fluorine-containing hydrophobic component and the ultraviolet shielding functional filler are introduced at the same time, the ultraviolet aging resistance and the surface hydrophobicity of the film are synergistically improved, the preparation process is simple and efficient, and the method is suitable for the large-scale production of the insulating film for bus ducts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulating film material preparation technology, specifically a method for preparing weather-resistant polyimide insulating films for busbar trunking through blending modification. Background Technology

[0002] Busbar trunking, as a highly efficient power transmission and distribution device, plays an irreplaceable role in power supply and distribution systems in high-rise buildings, large industrial plants, data centers, and rail transportation. With the continuous increase in electricity load and the increasing integration of power systems, the performance requirements for the internal insulation materials of busbar trunking systems are becoming increasingly stringent. As the key dielectric material for phase-to-phase insulation and phase-to-ground insulation in busbar trunking, the insulation film's heat resistance, insulation strength, mechanical toughness, and environmental tolerance under long-term operating conditions directly affect the operational safety and service life of the entire power distribution system.

[0003] Polyimide film, with its excellent high-temperature resistance, outstanding electrical insulation properties, and good mechanical strength, has been widely used in high-end technology fields such as aerospace, electronic information, and electrical insulation. In busbar trunking applications, polyimide film can operate stably for extended periods above 200℃, and its short-term temperature resistance can reach above 400℃. Its dielectric strength is typically much higher than that of conventional polymer insulation materials, making it an ideal choice for busbar trunking insulation layers. However, in practical engineering applications, it has been found that conventional polyimide film exhibits significant performance shortcomings under long-term outdoor or semi-outdoor conditions. The installation environment of busbar trunking is often accompanied by alternating effects of sunlight, rain, industrial air pollution, drastic temperature changes, and humid air. Although the imide and aromatic ring structures in the conventional polyimide molecular chain give it excellent thermal stability, under long-term ultraviolet radiation, the molecular chain undergoes photo-oxidative degradation, leading to microcracks on the film surface and a gradual deterioration of insulation performance. At the same time, water molecules in the air, under the influence of an electric field, can easily form partial discharge channels at film defects, accelerating the aging process of the insulation material.

[0004] Currently, there is a large body of literature reporting on the modification of polyimide films, mainly involving strategies such as inorganic nanoparticle filling modification, introduction of fluorinated groups, and copolymer structure design. Nano-titanium dioxide, as a wide-bandgap semiconductor material, can effectively absorb and shield ultraviolet light. Simultaneously, its uniform dispersion in the polymer matrix can significantly enhance the chemical inertness of the composite film against reactive oxygen free radicals, thereby delaying the photo-oxidative aging rate. The introduction of fluorinated groups can reduce the surface free energy of the film, enhance its hydrophobic properties, and reduce the adsorption and penetration of water molecules on the film surface. However, in existing modification schemes, the problem of nanoparticle aggregation in the polyimide matrix has not been well resolved. Simple mechanical stirring is insufficient to achieve uniform dispersion at the nanoscale; agglomerates often become stress concentration points and electric field distortion regions, thus weakening the insulation and mechanical properties of the film. Regarding fluorine-containing modification, although fluorinated monomer copolymerization can effectively introduce fluorinated groups, the synthesis route is complex and costly, and excessive fluorine modification can sacrifice the inherent high bonding strength and mechanical properties of polyimide.

[0005] Furthermore, in existing polyimide film preparation processes, the temperature rise procedure during the imidization stage has a decisive impact on the final properties of the film. Excessively rapid heating rates or improper holding times can lead to the rapid vaporization of residual solvents inside the film, forming pore defects. Simultaneously, residual polyamic acid groups generated from incomplete imidization are prone to hydrolysis in humid and hot environments, reducing the film's long-term weather resistance. While step-heating strategies have been mentioned in some studies, systematic research is lacking on the compatibility of heating procedures for synergistic modification systems of fluorinated alkyl silanes and nano-titanium dioxide. The influence of different modifying components on imidization kinetics has not yet been fully revealed. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blending modification, so as to solve the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blending modification, the method comprising: Aromatic dianhydride monomers and aromatic diamine monomers are subjected to a condensation reaction in an aprotic polar solvent to generate a polyamic acid solution. A fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion were added to the polyamic acid solution and mechanically sheared and blended to obtain a modified polyamic acid blend. The modified polyamic acid blend was cast into a film and subjected to a step-by-step imidization treatment under an inert atmosphere to obtain a blended modified polyimide film.

[0008] Preferably, in the step of performing a polycondensation reaction of aromatic dianhydride monomer and aromatic diamine monomer in an aprotic polar solvent to generate a polyamic acid solution, The aromatic dianhydride monomer is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, or 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride. The aromatic diamine monomer is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane; The aprotic polar solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone. The molar ratio of the aromatic dianhydride monomer to the aromatic diamine monomer is 1:(0.98-1.02); The polycondensation reaction is carried out at a temperature of 0–10°C, for a reaction time of 6–24 hours, and the solid content in the reaction system is 10%–20%.

[0009] Preferably, in the step of performing a polycondensation reaction of aromatic dianhydride monomer and aromatic diamine monomer in an aprotic polar solvent to generate a polyamic acid solution, The aromatic dianhydride monomer is added to the reaction system in batches, with the total feeding time controlled within 2 to 4 hours. After each feeding, the stirring speed of the reaction system is adjusted to 200-400 rpm and stirred for 15-30 minutes. The aromatic diamine monomer is pre-dissolved in the aprotic polar solvent at a temperature of 25–40°C for 1–3 hours.

[0010] Preferably, in the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The amount of the fluorinated alkylsilane oligomer added is 2% to 8% of the solid weight in the polyamic acid solution; The amount of the nano-titanium dioxide dispersion added is 1% to 5% of the solid weight in the polyamic acid solution; The nano-titanium dioxide dispersion has a particle size of 10-50 nanometers, and the dispersion medium is the aprotic polar solvent. The mechanical shearing blending was carried out using a high-shear emulsifier with a shearing speed of 3000-6000 rpm and a shearing time of 30-60 minutes. During the shearing process, the temperature of the reaction system was maintained at 15-30°C.

[0011] Preferably, in the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The fluorinated alkyl silane oligomer is at least one of heptadecafluorodecyltrimethoxysilane oligomer, tridecafluorooctyltriethoxysilane oligomer, or nonafluorohexyltrimethoxysilane oligomer, and its number average molecular weight is 1000-5000. The fluorinated alkylsilane oligomer is pre-dissolved in the aprotic polar solvent before being added to prepare a premixed solution with a mass concentration of 10% to 30%. The premixed solution is prepared at a temperature of 20 to 35°C and a stirring time of 10 to 20 minutes.

[0012] Preferably, in the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The preparation method of the nano-titanium dioxide dispersion is as follows: The nano-titanium dioxide powder is mixed with the aprotic polar solvent at a mass ratio of 1:(5-15), and a dispersant of 0.5% to 2% of the weight of the nano-titanium dioxide powder is added. The dispersant is at least one of polyvinylpyrrolidone, polyethylene glycol or sodium dodecylbenzenesulfonate. The mixed materials are placed in an ultrasonic dispersion device with an ultrasonic frequency of 20-40 kHz, an ultrasonic power of 100-300 W, and an ultrasonic dispersion time of 20-40 minutes to obtain the nano-titanium dioxide dispersion.

[0013] Preferably, in the step of casting the modified polyamic acid blend into a film and performing a step-by-step heating imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The film casting process employs a doctor blade coating method, with a gap of 100–300 micrometers between the doctor blade and the casting substrate. The temperature of the casting substrate is controlled at 20-30°C, and the casting speed is 0.5-2 meters / minute. After casting, the wet film is dried at 50–80°C for 30–60 minutes under the protection of the inert atmosphere, and then enters the step-heat imidization treatment.

[0014] Preferably, in the step of casting the modified polyamic acid blend into a film and performing a step-by-step heating imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The stepped heating imidization process comprises four temperature stages: The first temperature stage is 100-130℃, and the holding time is 20-40 minutes; The second temperature stage is 160–190℃, and the holding time is 15–30 minutes; The third temperature stage is 220-250℃, and the holding time is 10-20 minutes; The fourth temperature stage is 280–320℃, and the holding time is 5–15 minutes; The heating rate between two adjacent temperature stages is 2–5 °C / min.

[0015] Preferably, in the step of casting the modified polyamic acid blend into a film and performing a step-by-step heating imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The inert atmosphere is nitrogen or argon, and the flow rate is 1 to 5 liters per minute; During the step-heat imidization process, the absolute pressure inside the reaction chamber is controlled at 0.05–0.1 MPa. After the fourth temperature stage is completed, the film is cooled to 60-80°C at a cooling rate of 1-3°C / minute, and then naturally cooled to room temperature.

[0016] Preferably, after the step of casting the modified polyamic acid blend into a film and performing a stepwise heating imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, the method further includes a step of biaxially stretching the blended modified polyimide film. The biaxial stretching treatment is performed after the third temperature stage of the stepped heating imidization treatment. The longitudinal tensile ratio of biaxial tension is 1.5 to 3.0, and the transverse tensile ratio is 1.5 to 3.0. The stretching rate of biaxial tensioning is 5–20 mm / min; After the biaxial stretching treatment is completed, the temperature is raised to the fourth temperature stage for subsequent imidization treatment.

[0017] Compared with the prior art, the beneficial effects of the present invention are: This invention creatively employs fluorinated alkylsilane oligomers and nano-titanium dioxide dispersions as blending modifiers, introducing them into a polyamic acid solution system for high-shear mechanical blending. The fluorinated alkylsilane oligomers contain active silanol groups or hydrolyzable alkoxy groups, which, during blending and subsequent high-temperature imidization treatment, can undergo condensation reactions with carboxyl or hydroxyl groups on the polyamic acid molecular chain, chemically grafting them onto the polyimide molecular backbone. This achieves permanent fixation of the fluorinated component, avoiding the migration and precipitation problems of fluorinated additives associated with physical blending. Simultaneously, the active hydroxyl groups on the surface of the nano-titanium dioxide can also undergo coupling reactions with the fluorinated alkylsilane oligomers, forming an organic-inorganic crosslinked network structure. This structure constructs a three-dimensional chemical crosslinked system within the film, significantly enhancing the interfacial bonding strength between the modified component and the matrix.

[0018] Regarding improved weather resistance, the nano-titanium dioxide component can efficiently absorb ultraviolet light in the wavelength range of 280 nm to 380 nm, converting ultraviolet light energy into heat energy or dissipating it through an electronic excitation-relaxation process. This significantly reduces the number of high-energy photons reaching the polyimide molecular chain backbone, effectively inhibiting photo-oxidative degradation reactions from the energy transfer path. After imidization treatment, the fluorinated alkyl silane oligomers exhibit directional enrichment and orderly arrangement of fluorinated alkyl segments on the film surface, forming a hydrophobic surface layer with low surface energy. The synergistic effect of this surface layer and nano-titanium dioxide maintains the surface cleanliness of the film in humid and polluted environments, reducing the risk of surface flashover caused by dirt adhesion and moisture infiltration.

[0019] For the overall insulation reliability of the film, the introduction of fluorinated alkylsilane oligomers can effectively passivate active defect sites inside and on the surface of the polyimide film, reduce charge trap density, and achieve a uniform electric field distribution. The appropriate introduction of nano-titanium dioxide improves the uniformity of the dielectric constant of the film to a certain extent, avoiding electric field concentration caused by abrupt changes in local dielectric properties. Through a high-shear mechanical blending process, nano-titanium dioxide particles are forcibly dispersed into a primary particle state at the nanoscale within the polyamic acid matrix. Combined with the surface modification effect of the fluorinated alkylsilane oligomers, this effectively suppresses the tendency for nanoparticle re-aggregation, ensuring the uniformity of the internal structure of the composite film. Attached Figure Description

[0020] Figure 1 This diagram illustrates the working steps of the method for preparing a weather-resistant polyimide insulating film for busbar trunking according to the present invention. Detailed Implementation

[0021] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Simple modifications, equivalent substitutions, and parameter optimizations made to the present invention by those skilled in the art without departing from the core technical concept of the present invention all fall within the scope of protection of the present invention.

[0022] This invention provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blend modification. The core process involves preparing a polyamic acid matrix through low-temperature polycondensation of aromatic dianhydrides and aromatic diamines, followed by a dual-modification system of fluorinated alkyl silane oligomers and nano-titanium dioxide. This is combined with high-shear blending, precise casting, inert atmosphere stepwise imidization, and controllable biaxial stretching processes to prepare a polyimide insulating film specifically for busbar trunking that exhibits excellent electrical insulation, weather resistance, and mechanical stability. All embodiments and comparative examples employ uniform testing standards: weather resistance is tested using ultraviolet aging (wavelength 340 nm, irradiation intensity 0.89 W / (m²·nm), aging time 1000 h), measuring the film's tensile strength retention rate and transmittance attenuation rate; electrical performance is tested using power frequency breakdown voltage and volume resistivity; and mechanical performance is tested using tensile strength and elongation at break.

[0023] Example 1 See appendix Figure 1 This embodiment provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blend modification. The specific steps are as follows: (1) Preparation of polyamic acid solution: The aromatic dianhydride monomer was selected as 3,3',4,4'-biphenyltetracarboxylic dianhydride, the aromatic diamine monomer was selected as 4,4'-diaminodiphenyl ether, and the aprotic polar solvent was N-methylpyrrolidone. The molar ratio of aromatic dianhydride monomer to aromatic diamine monomer was controlled at 1:1.0, and the solid content of the reaction system was 15%. First, 4,4'-diaminodiphenyl ether was added to N-methylpyrrolidone solvent and stirred at 30°C for 2 hours until the monomer was completely dissolved to form a transparent and homogeneous solution. 3,3',4,4'-biphenyltetracarboxylic dianhydride was added in batches, with a total feeding time of 3 hours. The addition was done in 6 equal batches. After each addition, the stirring speed was adjusted to 300 rpm and stirred continuously for 20 minutes to ensure that the monomer was fully dispersed. After the feed is completed, the temperature of the reaction system is kept constant at 5°C, and the polycondensation reaction is carried out in a closed system for 12 hours. After the reaction is completed, a uniform, transparent, and precipitate-free polyamic acid solution is obtained.

[0024] (2) Preparation of modified polyamic acid blend: The fluorinated alkyl silane oligomer was selected as tridecafluorooctyltriethoxysilane oligomer with a number average molecular weight of 3000. It was dissolved in N-methylpyrrolidone solvent and stirred at 25°C for 15 min to prepare a premix with a mass concentration of 20%. The premix was free of stratification and flocculent precipitate. The final amount of fluorinated alkyl silane oligomer added was 5% of the solid weight of the polyamic acid solution. Preparation of nano-titanium dioxide dispersion: 30 nm nano-titanium dioxide powder and N-methylpyrrolidone solvent were mixed at a mass ratio of 1:10. 1.2% of the weight of nano-titanium dioxide powder as dispersant polyvinylpyrrolidone was added. After mixing evenly, it was placed in an ultrasonic dispersion device. The ultrasonic frequency was set to 30 kHz and the ultrasonic power to 200 W. The mixture was ultrasonically dispersed at a constant temperature for 30 min to obtain a stable and uniform nano-titanium dioxide dispersion. The amount of nano-titanium dioxide dispersion added was 3% of the solid weight of the polyamic acid solution. The prepared fluorinated alkyl silane oligomer premix and nano titanium dioxide dispersion were sequentially added to the polyamic acid solution. Mechanical shearing and blending were performed using a high-shear emulsifier, with the shearing speed controlled at 4500 rpm and the shearing time at 45 min. The system temperature was kept constant at 20℃ during the shearing process. After shearing, a fine, uniform modified polyamic acid blend without particle agglomeration was obtained.

[0025] (3) Casting and Pretreatment: Casting was performed using a doctor blade coating method. The gap between the doctor blade and the stainless steel substrate was set to 200 μm, the substrate temperature was kept constant at 25℃, and the casting speed was controlled at 1.0 m / min. The uniform wet film formed by casting was placed in a nitrogen inert atmosphere with a nitrogen flow rate of 3 L / min. It was first dried at 65℃ for 45 min to completely remove the residual solvent on the film surface and in the shallow layer, resulting in a semi-dry polyamic acid film without solvent bubbles or wrinkles.

[0026] (4) Stepwise heating imidization treatment: The dried film is placed in a closed imidization reaction chamber, the absolute pressure of which is controlled at 0.08 MPa, and nitrogen gas is continuously introduced for protection. A four-stage stepwise heating process is adopted, with the heating rate of adjacent stages being 3℃ / min. First stage: Heating to 115℃ and holding at that temperature for 30 min removes trace amounts of residual solvent inside the film and initially completes the relaxation and arrangement of molecular chains; Second stage: Heating to 175℃ and holding at that temperature for 20 min initiates the initial imidization reaction and forms a primary imide ring structure; Third stage: Heating to 235℃ and holding at that temperature for 15 min further promotes the imidization reaction and improves the molecular cross-linking structure; Fourth stage: Heating to 300℃ and holding at that temperature for 10 min completes the full imidization reaction and solidifies the overall structure of the film.

[0027] (5) Biaxial stretching and post-treatment: After the third temperature stage of heat preservation and before the fourth temperature stage of heating, the film is subjected to biaxial stretching treatment. The longitudinal stretching ratio is set to 2.0, the transverse stretching ratio is set to 2.0, and the stretching rate is 10 mm / min. The stretching process is uniform and stable, without any film tearing or uneven deformation. After stretching, the temperature is continued to rise to the fourth temperature stage to complete the final imidization. After imidization, the film is cooled to 70°C at a cooling rate of 2°C / min. Then the temperature control system is turned off, and the film is allowed to cool naturally to room temperature. After demolding, the finished weather-resistant polyimide insulating film for busbar trunking is obtained.

[0028] Example 2 This embodiment provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blend modification, the specific steps of which are as follows: (1) Preparation of polyamic acid solution: The aromatic dianhydride monomer was selected as pyromellitic dianhydride, the aromatic diamine monomer was selected as p-phenylenediamine, and the aprotic polar solvent was selected as N,N-dimethylacetamide. The molar ratio of aromatic dianhydride monomer to aromatic diamine monomer was controlled at 1:0.99, and the solid content of the reaction system was 12%. First, p-phenylenediamine was added to N,N-dimethylacetamide solvent and stirred at 28℃ for 1.5h until the monomer was completely dissolved. Pyromellitic dianhydride was added in batches, with a total feeding time of 2.5h. It was added in 5 equal batches. After each addition, the stirring speed was adjusted to 250 rpm and stirred continuously for 18min. After the addition was completed, the temperature of the reaction system was kept constant at 8℃, and the polycondensation reaction was carried out in a closed system for 18h to obtain a transparent and homogeneous polyamic acid solution.

[0029] (2) Preparation of modified polyamic acid blend: The fluorinated alkyl silane oligomer was selected as nonafluorohexyltrimethoxysilane oligomer with a number average molecular weight of 2000. It was dissolved in N,N-dimethylacetamide solvent and stirred at 22℃ for 12 min to prepare a premix with a mass concentration of 15%. The final amount of fluorinated alkyl silane oligomer added was 3% of the solid weight of the polyamic acid solution. Preparation of nano-titanium dioxide dispersion: Nano-titanium dioxide powder with a particle size of 20 nm was mixed with N,N-dimethylacetamide solvent at a mass ratio of 1:8. Polyethylene glycol dispersant accounting for 0.8% of the weight of nano-titanium dioxide powder was added. After mixing, ultrasonic dispersion was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 150 W, and an ultrasonic duration of 25 min to obtain a stable dispersion. The amount of nano-titanium dioxide dispersion added was 2% of the solid weight of the polyamic acid solution. Two modifying agents were added sequentially to a polyamic acid solution and blended using a high-shear emulsifier at a shearing speed of 3500 rpm for 35 min and a system temperature of 18°C ​​to obtain a uniform, non-agglomerated modified blend.

[0030] (3) Casting and pretreatment: The film was cast by a doctor blade with a gap of 150 μm, a substrate temperature of 22 °C, and a casting speed of 0.8 m / min. The formed wet film was dried at 60 °C for 35 min under nitrogen protection (flow rate 2 L / min) to remove residual solvent and obtain a smooth and defect-free semi-dry film.

[0031] (4) Stepwise heating imidization treatment: The film was placed in an imidization chamber with an absolute pressure of 0.06 MPa and nitrogen gas was continuously introduced for protection. The film underwent a four-stage stepwise heating process at a rate of 2.5 °C / min. Stage 1: 105 °C, held for 25 min; Stage 2: 165 °C, held for 18 min; Stage 3: 225 °C, held for 12 min; Stage 4: 290 °C, held for 8 min. Solvent removal and imidization reactions were steadily advanced in each stage to ensure uniform molecular structure formation.

[0032] (5) Biaxial stretching and post-treatment: After the third temperature stage of heat preservation, biaxial stretching is performed with a longitudinal stretching ratio of 1.8 and a transverse stretching ratio of 1.8, and a stretching rate of 8 mm / min. After stretching, the fourth stage of imidization treatment is carried out. After the reaction is completed, the temperature is reduced to 65°C at a rate of 1.5°C / min, and then naturally cooled to room temperature. The finished modified polyimide insulating film is then demolded.

[0033] Example 3 This embodiment provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blend modification, the specific steps of which are as follows: (1) Preparation of polyamic acid solution: The aromatic dianhydride monomer was selected as 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, the aromatic diamine monomer was selected as 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and the aprotic polar solvent was selected as N,N-dimethylformamide. The molar ratio of aromatic dianhydride monomer to aromatic diamine monomer was controlled at 1:1.01, and the solid content of the reaction system was 18%. The aromatic diamine monomer was added to the solvent and stirred at 35°C for 2.5 h to ensure complete dissolution. The dianhydride monomer was added in batches, with a total feeding time of 3.5 h. It was added in 7 equal batches. After each addition, the stirring speed was 350 rpm and the stirring was maintained for 25 min. After the addition was completed, the system was kept at a constant temperature of 3°C and the polycondensation reaction was carried out for 20 h to obtain a high-viscosity, uniform and transparent polyamic acid solution.

[0034] (2) Preparation of modified polyamic acid blend: The fluorinated alkyl silane oligomer was selected as heptadecafluorodecyltrimethoxysilane oligomer with a number average molecular weight of 4000. It was dissolved in N,N-dimethylformamide solvent at 30℃ and stirred for 18 min to prepare a premix with a mass concentration of 25%. The amount added was 7% of the solid weight of polyamic acid. Preparation of nano-titanium dioxide dispersion: The mass ratio of titanium dioxide powder with a particle size of 40 nm to solvent was 1:12. 1.8% sodium dodecylbenzenesulfonate was added as a dispersant. The ultrasonic frequency was 35 kHz, the ultrasonic power was 250 W, and the ultrasonic dispersion was carried out for 35 min. The amount of dispersion added was 4% of the solid weight of polyamic acid. The premix of additives was added to the matrix solution. The high shear mixing speed was 5500 rpm, the shearing time was 55 min, and the system temperature was 28℃ to obtain a uniform and stable modified blend.

[0035] (3) Casting and pretreatment: The doctor blade coating gap is 250 μm, the substrate temperature is 28℃, and the casting speed is 1.8 m / min. The wet film is dried at 75℃ for 55 min under argon protection (flow rate 4 L / min) to completely remove the shallow solvent, and the film surface is smooth and without defects.

[0036] (4) Stepwise heating imidization treatment: The absolute pressure of the chamber is 0.09 MPa, and argon gas is continuously introduced for protection. The heating rate is 4℃ / min. First stage: 125℃, hold for 35 min; Second stage: 185℃, hold for 28 min; Third stage: 245℃, hold for 18 min; Fourth stage: 310℃, hold for 12 min. Solvent removal, molecular chain solidification, and imidization ring-closing reaction are completed step by step.

[0037] (5) Biaxial stretching and post-treatment: After the third stage of heat preservation, biaxial stretching was performed with a longitudinal and transverse stretching ratio of 2.8 and a stretching rate of 18 mm / min. After stretching, the fourth stage of curing was carried out. After the reaction was completed, the temperature was reduced to 75°C at a cooling rate of 2.5°C / min, and then allowed to cool naturally to room temperature before demolding to obtain the finished film.

[0038] Example 4 This embodiment provides a method for preparing a weather-resistant polyimide insulating film for busbar trunking through blend modification, the specific steps of which are as follows: (1) Preparation of polyamic acid solution: A composite monomer system was selected. The aromatic dianhydride monomers were 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenyl ethertetracarboxylic dianhydride mixed at a mass ratio of 1:1. The aromatic diamine monomers were 4,4'-diaminodiphenyl ether and p-phenylenediamine mixed at a mass ratio of 1:1. The aprotic polar solvent was N-methylpyrrolidone and N,N-dimethylacetamide mixed at a volume ratio of 1:1. The molar ratio of dianhydride to diamine monomers was 1:1.02, and the solid content of the system was 20%. The mixed diamine monomers were added to the composite solvent and stirred at 32°C for 2 hours to dissolve. The composite dianhydride monomers were added in batches, with a total feeding time of 4 hours. After each feeding, the mixture was stirred at 400 rpm for 30 minutes. After the feeding was completed, the polycondensation reaction was carried out at 0°C for 24 hours to obtain a highly stable polyamic acid solution.

[0039] (2) Preparation of modified polyamic acid blend: A premix of composite fluorinated alkyl silane oligomers (tridecylfluorooctyltriethoxysilane oligomer + nonafluorohexyltrimethoxysilane oligomer in a mass ratio of 1:1) with a number average molecular weight of 2500 was prepared with a mass concentration of 30% and the amount added was 8% of the solid weight of polyamic acid. The nano-titanium dioxide dispersion was prepared by using 50nm particle size powder, with a mass ratio of 1:15 with the solvent, and 2% polyvinylpyrrolidone was added. The dispersion was ultrasonically dispersed at 40kHz and 300W for 40min and the amount added was 5% of the solid weight of polyamic acid. The high-shear blending speed was 6000 rpm, the shearing time was 60min, and the system temperature was 30℃ to obtain a highly uniform modified blend.

[0040] (3) Casting and pretreatment: The doctor blade gap was 300 μm, the substrate temperature was 30℃, and the casting speed was 2.0 m / min. The wet film was dried at 80℃ for 60 min under nitrogen flow rate of 5 L / min protection to complete the pre-drying treatment.

[0041] (4) Stepwise heating imidization treatment: Absolute pressure of the chamber is 0.1 MPa, nitrogen protection is provided, and the heating rate is 5℃ / min. First stage: 130℃, hold for 40 min; Second stage: 190℃, hold for 30 min; Third stage: 250℃, hold for 20 min; Fourth stage: 320℃, hold for 15 min, to completely complete the imidization reaction.

[0042] (5) Biaxial stretching and post-treatment: After the third stage, biaxial stretching was performed with a longitudinal and transverse stretching ratio of 3.0 and a stretching rate of 20 mm / min. After stretching, final curing was completed, and the temperature was reduced to 80°C at 3°C / min. The film was then allowed to cool naturally to room temperature to obtain the finished modified film.

[0043] Comparative Example 1 This comparative example provides a method for preparing polyimide films, which differs from Example 1 in that: no fluorinated alkyl silane oligomer and nano-titanium dioxide dispersion are added; instead, a pure polyamic acid solution is used to prepare the film. All other process parameters and operating steps are completely consistent with Example 1. The specific steps are as follows: (1) Preparation of polyamic acid solution: The monomer type, ratio, solvent, reaction temperature, time and feeding method are the same as in Example 1, and a pure polyamic acid solution is prepared.

[0044] (2) Casting and pretreatment: Pure polyamic acid solution was directly used for doctor blade coating and casting. The process parameters were exactly the same as in Example 1, and the wet film drying conditions were the same.

[0045] (3) The step-heat imidization, biaxial stretching and post-treatment processes are exactly the same as in Example 1, and finally an unmodified pure polyimide insulating film is obtained.

[0046] Comparative Example 2 This comparative example provides a method for preparing polyimide films, which differs from Example 1 in that only nano-titanium dioxide dispersion is added, without the addition of fluorinated alkyl silane oligomers. The addition of modifying agents, dispersion process, and other preparation parameters are the same as in Example 1. The specific steps are as follows: (1) The preparation process of polyamic acid solution is completely consistent with that of Example 1.

[0047] (2) Add only nano-titanium dioxide dispersion with the same parameters as in Example 1 to the polyamic acid solution, without adding fluorinated alkyl silane oligomers, and obtain a single-modified polyamic acid blend through the same high-shear blending process.

[0048] (3) The casting, drying, imidization, biaxial stretching and post-treatment processes are the same as in Example 1, and a single nano-titanium dioxide modified polyimide insulating film is obtained.

[0049] Comparative Example 3 This comparative example provides a method for preparing polyimide film, which differs from Example 1 in that: the stepped heating imidization process is omitted, and a conventional one-step heating imidization treatment is used. The remaining raw materials, proportions, blending, casting, and stretching processes are the same as in Example 1. The specific steps are as follows: (1) The preparation process of polyamic acid solution and modified blend is exactly the same as that in Example 1.

[0050] (2) The casting and pretreatment process is the same as in Example 1, and a semi-dry film is obtained after drying.

[0051] (3) Imidification treatment: The dried film was directly heated to 300°C and kept at a constant temperature for 60 minutes to complete the imidization. The heating rate, atmosphere conditions, and chamber pressure were the same as in Example 1, without the segmented step heating process.

[0052] (4) The biaxial stretching and post-processing process is the same as in Example 1, and the modified polyimide film prepared by conventional imidization process is obtained.

[0053] The polyimide insulating films prepared in the above four examples and three comparative examples were subjected to uniform performance testing. The weather resistance, electrical insulation performance and mechanical properties of the films were tested respectively. The test data are summarized in the following table and analyzed in detail.

[0054] Table 1: Weather resistance test data of films in each embodiment and comparative example (UV aging for 1000h) The weathering performance test data after 1000 hours of UV aging shows that the modified polyimide films prepared in Examples 1-4 of this invention exhibit significantly better weather resistance than the comparative samples. Example 4 demonstrates the best overall weather resistance, with a tensile strength retention rate of 94.2% and a transmittance attenuation rate of only 6.8%, the best among all samples. Compared to the unmodified Comparative Example 1, Example 4 shows a 16.8 percentage point increase in tensile strength retention and a 15.5 percentage point decrease in transmittance attenuation after aging, proving that the composite modification system of fluorinated alkyl silane oligomers and nano-titanium dioxide can significantly improve the UV aging resistance of polyimide films.

[0055] Comparative Example 2, with only nano-titanium dioxide as a single modifier, showed a slight improvement in weather resistance compared to the pure film Comparative Example 1, but it was far inferior to the dual-modified systems of Examples 1-4. This indicates that nano-titanium dioxide only serves as a UV shield, while the fluorinated alkyl silane oligomer can optimize the film surface density and reduce the rate of molecular chain aging and degradation. The combination of the two has a significant synergistic effect. Comparative Example 3, which eliminated the step-by-step heating imidization process and adopted a one-time heating curing method, showed significantly lower weather resistance than Example 1. This is because one-time heating easily leads to solvent residue inside the film, uneven molecular cross-linking, and incomplete imidization. During aging, defect sites are prone to degradation, significantly reducing weather resistance stability.

[0056] It can also be seen that with the increase of the amount of modified additives and the application of composite monomers and composite solvent systems (Example 4), the initial mechanical properties and weather resistance stability of the film are improved simultaneously. Under the gradient parameter setting, the high-ratio modified systems of Examples 3 and 4 have better weather resistance than Examples 1 and 2, and are suitable for the complex service environment of busbar trunking under long-term outdoor, high temperature and ultraviolet radiation.

[0057] Table 2: Test data of electrical insulation performance of thin films in various embodiments and comparative examples Electrical insulation performance is a core indicator of busbar trunking insulation films, directly determining the power transmission safety and operational stability of the busbar trunking. Test data shows that the power frequency breakdown voltage of all samples in the embodiments of this invention is higher than 120kV / mm, and the volume resistivity is greater than 7.9×10¹. 6 The insulation resistance (Ω·cm) of all components meets Class A insulation standards, satisfying the insulation requirements for high-voltage busbar trunking. Example 4 exhibits the best electrical performance, with a power frequency breakdown voltage of 135.8 kV / mm and a volume resistivity of 9.8 × 10¹⁸. 6 Ω·cm.

[0058] The pure polyimide film in Comparative Example 1 had a power frequency breakdown voltage of only 98.5 kV / mm and a volume resistivity significantly lower than the modified sample, only meeting the Class B insulation standard and unsuitable for high-voltage busbar trunking conditions. Comparative Example 2, with the addition of nano-titanium dioxide alone, showed improved electrical performance, but still lagged significantly behind the dual-modification system. This is because the fluorinated alkylsilane oligomer can fill the molecular gaps in the film, reducing internal porosity and inhibiting carrier migration, thus significantly improving insulation performance. Nano-titanium dioxide can optimize the dielectric stability of the film; the synergistic effect of both maximizes the improvement in electrical insulation performance.

[0059] Comparative Example 3, lacking a stepped heating imidization process, exhibited trace solvent residues and molecular structural defects within the film, making it prone to partial discharge under an electric field. Consequently, its breakdown voltage and volume resistivity were lower than those of Example 1, demonstrating that the segmented stepped heating process can achieve gradual solvent removal, ordered cross-linking of molecular chains, and complete imidization, effectively eliminating internal insulation defects and ensuring stable electrical performance. Meanwhile, Example 4, with its composite monomer, composite solvent, and high-ratio modifying agent, exhibited a denser molecular structure, fewer insulation defects, and achieved optimal electrical performance.

[0060] Table 3: Test data of mechanical properties of thin films in each embodiment and comparative example Mechanical properties and dimensional stability directly affect the installation adaptability and long-term operational reliability of the busbar trunking insulation film. During service, busbar trunking experiences temperature fluctuations, mechanical vibrations, and assembly tension, requiring the film to possess high strength, high toughness, and low thermal shrinkage. Test data shows that the tensile strength and elongation at break of Examples 1-4 of this invention are significantly higher than those of the comparative examples, and the thermal shrinkage rate is less than 0.4%, demonstrating excellent dimensional stability.

[0061] Example 4 exhibits the best mechanical properties, with a tensile strength of 195.2 MPa, an elongation at break of 32.3%, and a thermal shrinkage rate of only 0.25%. This is attributed to the optimized molecular chain flexibility and cross-linking density achieved through the composite monomer system, the filling of molecular defects by a high-ratio dual-modification additive, and the further regularization of the molecular chain arrangement by the high-ratio biaxial stretching process, which significantly improves the film's mechanical toughness and structural stability. Comparative Example 1, consisting of a pure film, exhibits the worst mechanical properties, with low tensile strength, insufficient toughness, and a high thermal shrinkage rate. It is prone to deformation, cracking, and detachment under high-temperature conditions, failing to meet the long-term operation requirements of the busbar trunking.

[0062] Comparative Example 2 shows that single nano-modification has limited effect on improving mechanical properties, demonstrating that the surface modification and cross-linking enhancement of fluorinated silane oligomers are crucial for improving the mechanical properties of the film. The two-component compound can achieve the dual effect of rigid particle toughening and organic molecule cross-linking enhancement. Comparative Example 3 eliminates the step-by-step imidization process, resulting in uneven cross-linking of film molecules and greater internal residual stress. Therefore, its mechanical toughness and dimensional stability are significantly lower than those of Example 1. This indicates that step-by-step heating can gradually release the internal stress of the film, achieving full relaxation, cross-linking, and ring closure of the molecular chains. Combined with a precise biaxial stretching process, a uniform and dense three-dimensional network structure is constructed, fundamentally improving the mechanical properties and thermal stability of the film.

[0063] This invention ensures the uniformity and stability of the polyamic acid matrix by precisely controlling the condensation reaction parameters of aromatic monomers; simultaneously improves the weather resistance, insulation, and mechanical properties of the film through the synergistic effect of the dual-modification system of fluorinated alkyl silane oligomers and nano-titanium dioxide; completely solves the problem of nanoparticle agglomeration through a high-shear low-temperature blending process, ensuring uniform dispersion of the modified system; achieves gradual solvent removal, internal stress release, and complete imidization reaction through an inert atmosphere stepwise heating imidization process, eliminating film structural defects; and regulates the molecular chain structure through a segmented biaxial stretching process, significantly improving the mechanical stability and dimensional accuracy of the film.

[0064] The performance defects of each comparative example fully verify the necessity of the core technical features of this invention: the unmodified system cannot resist ultraviolet aging and has insufficient insulation performance; the performance improvement of a single modified system is limited and cannot achieve synergistic optimization of multiple properties; the conventional one-time imidization process is prone to structural defects, reducing the overall stability of the film. The polyimide insulating film prepared in the embodiments of this invention meets or even exceeds the industry standards for busbar trunking insulation materials in all performance indicators, and has extremely strong weather resistance, electrical safety and mechanical reliability, making it suitable for large-scale industrial production and long-term complex operating conditions of busbar trunking.

[0065] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing weather-resistant polyimide insulating film for busbar trunking through blending modification, characterized in that, The method includes the following steps: Aromatic dianhydride monomers and aromatic diamine monomers are subjected to a condensation reaction in an aprotic polar solvent to generate a polyamic acid solution. A fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion were added to the polyamic acid solution and mechanically sheared to obtain a modified polyamic acid blend. The modified polyamic acid blend was cast into a film and subjected to a step-by-step imidization treatment under an inert atmosphere to obtain a blended modified polyimide film. In the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The amount of the fluorinated alkylsilane oligomer added is 2% to 8% of the solid weight in the polyamic acid solution; The amount of the nano-titanium dioxide dispersion added is 1% to 5% of the solid weight in the polyamic acid solution; The nano-titanium dioxide dispersion has a particle size of 10-50 nanometers, and the dispersion medium is the aprotic polar solvent. The mechanical shearing blending was carried out using a high-shear emulsifier with a shearing speed of 3000-6000 rpm and a shearing time of 30-60 minutes. During the shearing process, the temperature of the reaction system was maintained at 15-30°C. In the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The fluorinated alkyl silane oligomer is at least one of heptadecafluorodecyltrimethoxysilane oligomer, tridecafluorooctyltriethoxysilane oligomer, or nonafluorohexyltrimethoxysilane oligomer, and its number average molecular weight is 1000-5000. The fluorinated alkylsilane oligomer is pre-dissolved in the aprotic polar solvent before being added to prepare a premixed solution with a mass concentration of 10% to 30%. The premixed solution is prepared at a temperature of 20 to 35°C and a stirring time of 10 to 20 minutes.

2. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 1, characterized in that, In the step of performing a polycondensation reaction of aromatic dianhydride monomers and aromatic diamine monomers in an aprotic polar solvent to generate a polyamic acid solution... The aromatic dianhydride monomer is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, or 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride. The aromatic diamine monomer is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane; The aprotic polar solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone. The molar ratio of the aromatic dianhydride monomer to the aromatic diamine monomer is 1:(0.98-1.02); The polycondensation reaction is carried out at a temperature of 0–10°C, for a reaction time of 6–24 hours, and the solid content in the reaction system is 10%–20%.

3. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 2, characterized in that, In the step of performing a polycondensation reaction of aromatic dianhydride monomers and aromatic diamine monomers in an aprotic polar solvent to generate a polyamic acid solution... The aromatic dianhydride monomer is added to the reaction system in batches, with the total feeding time controlled within 2 to 4 hours. After each feeding, the stirring speed of the reaction system is adjusted to 200-400 rpm and stirred for 15-30 minutes. The aromatic diamine monomer is pre-dissolved in the aprotic polar solvent at a temperature of 25–40°C for 1–3 hours.

4. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 1, characterized in that, In the step of adding a fluorinated alkyl silane oligomer and a nano-titanium dioxide dispersion to the polyamic acid solution and performing mechanical shear blending to obtain a modified polyamic acid blend, The preparation method of the nano-titanium dioxide dispersion is as follows: The nano-titanium dioxide powder is mixed with the aprotic polar solvent at a mass ratio of 1:(5-15), and a dispersant of 0.5% to 2% of the weight of the nano-titanium dioxide powder is added. The dispersant is at least one of polyvinylpyrrolidone, polyethylene glycol or sodium dodecylbenzenesulfonate. The mixed materials are placed in an ultrasonic dispersion device with an ultrasonic frequency of 20-40 kHz, an ultrasonic power of 100-300 W, and an ultrasonic dispersion time of 20-40 minutes to obtain the nano-titanium dioxide dispersion.

5. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 1, characterized in that, In the step of casting the modified polyamic acid blend into a film and performing a step-by-step imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The film casting process employs a doctor blade coating method, with a gap of 100–300 micrometers between the doctor blade and the casting substrate. The temperature of the casting substrate is controlled at 20-30°C, and the casting speed is 0.5-2 meters / minute. After casting, the wet film is dried at 50–80°C for 30–60 minutes under the protection of the inert atmosphere, and then enters the step-heat imidization treatment.

6. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 5, characterized in that, In the step of casting the modified polyamic acid blend into a film and performing a step-by-step imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The stepped heating imidization process comprises four temperature stages: The first temperature stage is 100-130℃, and the holding time is 20-40 minutes; The second temperature stage is 160–190℃, and the holding time is 15–30 minutes; The third temperature stage is 220-250℃, and the holding time is 10-20 minutes; The fourth temperature stage is 280–320℃, and the holding time is 5–15 minutes; The heating rate between two adjacent temperature stages is 2–5 °C / min.

7. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 6, characterized in that, In the step of casting the modified polyamic acid blend into a film and performing a step-by-step imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, The inert atmosphere is nitrogen or argon, and the flow rate is 1 to 5 liters per minute; During the step-heat imidization process, the absolute pressure inside the reaction chamber is controlled at 0.05–0.1 MPa. After the fourth temperature stage is completed, the film is cooled to 60-80°C at a cooling rate of 1-3°C / minute, and then naturally cooled to room temperature.

8. The method for preparing weather-resistant polyimide insulating film for busbar trunking according to claim 7, characterized in that, After the step of casting the modified polyamic acid blend into a film and performing a stepped heating imidization treatment under an inert atmosphere to obtain a blended modified polyimide film, the method further includes a step of biaxially stretching the blended modified polyimide film. The biaxial stretching treatment is performed after the third temperature stage of the stepped heating imidization treatment. The longitudinal tensile ratio of biaxial tension is 1.5 to 3.0, and the transverse tensile ratio is 1.5 to 3.

0. The stretching rate of biaxial tensioning is 5–20 mm / min; After the biaxial stretching treatment is completed, the temperature is raised to the fourth temperature stage for subsequent imidization treatment.

Citation Information

Patent Citations

  • Nano-TiO2 / polyimide composite membrane and preparation method thereof

    CN106497054A